2017
DOI: 10.1073/pnas.1714058114
|View full text |Cite
|
Sign up to set email alerts
|

Direct electrical stimulation of the amygdala enhances declarative memory in humans

Abstract: Emotional events are often remembered better than neutral events, a benefit that many studies have hypothesized to depend on the amygdala's interactions with memory systems. These studies have indicated that the amygdala can modulate memory-consolidation processes in other brain regions such as the hippocampus and perirhinal cortex. Indeed, rodent studies have demonstrated that direct activation of the amygdala can enhance memory consolidation even during nonemotional events. However, the premise that the amyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
102
3
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 144 publications
(119 citation statements)
references
References 55 publications
3
102
3
2
Order By: Relevance
“…Our results are in line with previous studies showing that AMY activity at encoding increases the likelihood of remembering emotional, but not neutral items 48,49 , even without a conscious emotional experience 50 . However, the current study is the first to show that AMY differentially contributes to memory for two distinct negative emotions, even after controlling for arousal level 51 .…”
Section: Differences In Memory Modulation By Disgust and Fearsupporting
confidence: 93%
“…Our results are in line with previous studies showing that AMY activity at encoding increases the likelihood of remembering emotional, but not neutral items 48,49 , even without a conscious emotional experience 50 . However, the current study is the first to show that AMY differentially contributes to memory for two distinct negative emotions, even after controlling for arousal level 51 .…”
Section: Differences In Memory Modulation By Disgust and Fearsupporting
confidence: 93%
“…Results predominantly show that applying electrical stimulation to the hippocampus and entorhinal cortex impairs memory (11,15) (with some exceptions (10)), providing evidence for causal role of these regions in mnemonic processing. This makes DBS ideal for studying cognitive enhancement and causal roles of deep cortical structures associated with memory (7--14, 16) and sensory processes (17,18) as well as for developing neuromodulation strategies to treat memory and motors disorders (19).…”
Section: Introductionmentioning
confidence: 99%
“…the subject perceived faces more positively when stimulation was applied as compared when it was off (Bijanki et al 2014). Second, Inman et al reported in fourteen patients that stimulation of the amygdala during perception of neutral stimuli enhanced subsequent delayed memory for the stimuli (Inman et al 2018). The investigators postulated that stimulation induced interactions between the amygdala, hippocampus, and entorhinal cortex.…”
Section: Introductionmentioning
confidence: 99%